Interaction of matrix metalloproteinase‐9 and Zpx in Cronobacter turicensis LMG 23827T mediated infections in the zebrafish model. (3rd August 2018) - Eshwar, Athmanya Konegadde; Wolfrum, Nina; Stephan, Roger; Fanning, Séamus; Lehner, Angelika
Abstract: Bacteria belonging to the genus Cronobacter have been recognized as causative agents of life‐threatening systemic infections primarily in premature and low‐birthweight neonates. Validation of putative bacterial virulence components as well as host factors potentially involved in the response to infection has been hampered in the past by the availability of suitable neonatal animal models. In the current study, the zebrafish embryo model was employed to study the interaction of the zinc metalloproteinase Zpx present in Cronobacter turicensis LMG 23827 T, with the eukaryotic MMP‐9, a proteinase that functions to cleave extracellular matrix gelatin and collagen. Cleavage and activation of the human recombinant pro‐MMP‐9 by zpx‐ expressing C. turicensis cells were demonstrated in vitro, and the presence and increase of the processed, active form of zebrafish pro‐MMP‐9 were shown in vivo. We provided evidence that Zpx induces the expression of the mmp‐9 but also increases the levels of processed MMP‐9 during infection. The involvement of the MMP‐9 in induction of the expression of the bacterial Zpx was shown in zebrafish mmp‐9 morphant experiments. This study identified MMP‐9 as a substrate of Zpx and demonstrated yet‐undescribed mutual cross‐talk between these two proteases in infections mediated by C. turicensis LMG 23827 T . Abstract : In this study the interaction of the bacterial zinc metallo protease Zpx with host MMP‐9 in infections mediated by the human pathogen C. turicensis was studied in vitro and in vivo using the zebrafish embryo model. Evidence was provided that presence of Zpx leads to an increase of the activated form of the MMP‐9 which may lead to adverse effects by tipping the balance between repair and destruction of extracellular tissues executed by this eukaryotic protease.